Aplikasi Pengolahan Data Sertifikat Tanah Pada Kantor Badan Pertanahan Nasional Kabupaten Bireuen Berbasis Java - Iqbal; Wahyu Ahmad Rahman (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The National Land Agency of Bireuen Regency has several divisions, one of which is the land certification division. Processing of land certificate data, namely land registration activities for the first time simultaneously which includes all land registration objects that have not been registered in the territory or part of the territory of a village or sub-district because they still use the conventional method, namely by recording on the bookkeeping media so that it takes quite a long time to process. data processing, besides that in data archiving, damage often occurs and even data loss is considered ineffective and inefficient. This study aims to produce an application that can facilitate land certification staff in processing data and searching for the necessary archives so that it does not take a long time. With the existence of a Java-based data processing application that can help simplify the data processing process at the national land agency, Bireuen district, land certification division. For that we need a system that can facilitate the performance of employees in the treatment of data processing. The system in question is the Data Processing System for the Registration of Land Rights Applications. This application is built using the Java Netbeans programming language and uses a MySQL database. So that the stored data is safer and more secure.